Frequency of Hyponatremic Dehydration in Children (6-59 Months) Presenting with Acute Gastroenteritis in a Tertiary Care Facility: Hyponatremic Dehydration in Children (6-59 Months) Presenting with Acute Gastroenteritis - Dhillon, Ali Imran; Ahsan, Saima; Fatima, Syeda Gohar; Najeeb, Nayra; Chaudhary, Tanveer Ahmad; Soomro, Abdul Hafeez; Ahmed, Hadeeqa (Pakistan Journal of Health Sciences, 2026)
Acute gastroenteritis (AGE) is one of the primary morbid and mortal causes among children under five years old, especially in low- and middle-income countries (LMICs). Objective: To determine the frequency of hyponatremic dehydration in children aged 6 to 59 months with acute gastroenteritis. Methods: The cross-sectional design was employed in the Pakistan Atomic Energy Commission (PAEC) General Hospital, Islamabad. Non-probability consecutive sampling of children aged 6-59 months of both genders with acute gastroenteritis over six months, from 1st August 2025 to 31st January, 2026, was used to enroll the children. The exclusion criteria were chronic diarrhea, previous administration of intravenous fluids, septic shock, severe malnutrition, chronic illness (CKD, CHD, RTA, CAH), or use of diuretic/steroids. SPSS version 25.0 was used to analyze data. The relationship between hyponatremia and clinical/sociodemographic variables was evaluated using a chi-square test, with p ≤ 0.005 considered significant. Results: Among the 113 children who participated in the study, hyponatremic dehydration was identified in 14.2% (95% CI: 8.1%-21.8%). The prevalence of hyponatremia was more common in children with severe dehydration, underweight nutritional condition, frequent stool frequency, incomplete rotavirus vaccination, and low socioeconomic status (p<0.005). Conclusions: Hyponatremic dehydration is a significant, yet not very widespread, complication in children with acute gastroenteritis. Morbidity needs to be reduced through preventive steps, such as rotavirus vaccination and education of caregivers.